GaAs high temperature optical constants and application to optical monitoring within the MOVPE environment - Allwood, D; Klipstein, P; Mason, N; Nicholas, R; Walker, P (Minerals, Metals and Materials Soc (TMS), 2000)
The real and imaginary components of the GaAs refractive index at temperatures between 20-700 degrees C have been obtained. Measurements were made by comparing the variable angle reflectivity of p-polarized and s-polarized 633 nm wavelength light from a deoxidized GaAs surface. By using these temperature-dependent optical constants for GaAs, modeling has allowed the behavior of surface photoabsorption (SPA) signals with temperature and oxide layers present to be predicted for different angles of incidence. The experimentally observed SPA signals during deoxidization of GaAs show strong qualitative agreement with these calculations at each of the angles of incidence considered. The measurement of data and application to modeling provides a platform for the measurement of temperature-dependent optical data for other III-V materials and for the investigation of deoxidation mechanisms.